Phylogenetic structure of alien plant species pools from European donor habitats. Issue 12 (31st August 2021) - Kalusová, Veronika; Padullés Cubino, Josep; Fristoe, Trevor S.; Chytrý, Milan; van Kleunen, Mark; Dawson, Wayne; Essl, Franz; Kreft, Holger; Mucina, Ladislav; Pergl, Jan; Pyšek, Petr; Weigelt, Patrick; et al.
Abstract: Aim: Many plant species native to Europe have naturalized worldwide. We tested whether the phylogenetic structure of the species pools of European habitats is related to the proportion of species from each habitat that has naturalized outside Europe (habitat's donor role) and whether the donated species are more phylogenetically related to each other than expected by chance. Location: Europe (native range), the rest of the world (invaded range). Time period: Last c . 100 years. Major taxa studied: Angiospermae. Methods: We selected 33 habitats in Europe and analysed their species pools, including 9, 636 plant species, of which 2, 293 have naturalized outside Europe. We assessed the phylogenetic structure of each habitat as the difference between the observed and expected mean pairwise phylogenetic distance (MPD) for (a) the whole species pool and (b) subgroups of species that have naturalized outside Europe and those that have not. We used generalized linear models to test for the effects of the phylogenetic structure and the level of human influence on the habitat's donor role. Results: Habitats strongly to moderately influenced by humans often showed phylogenetically clustered species pools. Within the clustered species pools, those species that have naturalized outside Europe showed a random phylogenetic structure. Species pools of less human‐influenced natural habitats varied from phylogenetically clustered to overdispersed, with donated naturalized species also often showing random patterns within the species pools. Donor roles in both habitat groups increased with increasing MPD within habitats. Main conclusions: European human‐influenced habitats donate closely related species that often naturalize in disturbed habitats outside their native range. Natural habitats donate species from different lineages with various ecological strategies that allow them to succeed in different habitats in the invaded range. However, the naturalized species donated by most European habitats are phylogenetically random subsets of their species pools.